2008
DOI: 10.1080/09687680802541169
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a CorA Mg2+transport channel fromMethanococcus jannaschiiusing a Thermofluor-based stability assay

Abstract: The Thermofluor assay has been a valuable asset in structural genomics, providing a high-throughput method for assessing the crystallizability of proteins. The technique has been well characterized for soluble proteins but has been less extensively described for membrane proteins. Here we show the successful application of a Thermofluor-based stability assay to an ion channel, CorA from Methanococcus jannaschii. Optimization of the concentration of free detergent within the assay was important, as excessive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…from three or more technical replicates of independent batches of proteoliposomes. www.nature.com/scientificreports www.nature.com/scientificreports/ (stabilization up to 95 °C) 40 . Altogether this might indicate that CoHex indeed binds to CorA proteins but either not with the high affinity or not exactly at the selectivity filter.…”
Section: Resultsmentioning
confidence: 99%
“…from three or more technical replicates of independent batches of proteoliposomes. www.nature.com/scientificreports www.nature.com/scientificreports/ (stabilization up to 95 °C) 40 . Altogether this might indicate that CoHex indeed binds to CorA proteins but either not with the high affinity or not exactly at the selectivity filter.…”
Section: Resultsmentioning
confidence: 99%
“…Thermofluor ® is an excellent candidate for this type of analysis, but suffers from the limitation that the fluorescent dyes used to determine the protein unfolding temperature interact with the detergent lipophilic moiety. This limitation makes the analysis difficult, if not impossible [20]. However, Thermo FAD allowed unfolding temperature analysis of a membrane‐anchored flavoprotein to be performed in the presence of detergents, because the flavin cofactor fluorescence is not influenced by these amphipathic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…SYPRO® Orange (Sigma–Aldrich) is known to show a bright fluorescence in presence of micelles,41 which results in a high initial fluorescence intensity. This problem was already reported in literature, especially in the field of membrane protein science 16,42–44. To overcome this problem, Kean et al43 carefully titrated the free surfactant concentration to a level with a sufficient signal‐to‐noise ratio, at which the determination of melting event was possible.…”
Section: Discussionmentioning
confidence: 99%
“…This problem was already reported in literature, especially in the field of membrane protein science. 16,[42][43][44] To overcome this problem, Kean et al 43 carefully titrated the free surfactant concentration to a level with a sufficient signal-to-noise ratio, at which the determination of melting event was possible. After this, Senisterra et al 42 demonstrated that DSLS is a suitable alternative to DSF with respect to the applicability of high-throughput thermal stability screenings in the presence of surfactants or notably hydrophobic proteins, such as membrane proteins, because no fluorescent probe is needed.…”
Section: The Surfactant Background Signalmentioning
confidence: 99%